In Vitro and In Vivo evaluation of a novel folate-targeted theranostic nanoemulsion of docetaxel for imaging and improved anticancer activity against ovarian cancers. Issue 7 (3rd July 2018) - Patel, Niravkumar R.; Piroyan, Aleksandr; Ganta, Srinivas; Morse, Allison B.; Candiloro, Katie M.; Solon, April L.; Nack, Abbegail H.; Galati, Corin A.; Bora, Collete; Maglaty, Marisa A.; O'Brien, Shane W.; Litwin, Samuel; et al.
ABSTRACT: Ovarian cancer ranks fifth in cancer related deaths for women in USA. The high mortality rate associated with ovarian cancer is due to diagnosis at later stages of disease and the high recurrence rate of 60–80%. Recurrent ovarian cancers are more likely to present as multidrug resistance (MDR) leading to unfavorable response from 2 nd and 3 rd line chemotherapy. Nanoemulsions (NEs) are emerging as an attractive drug delivery system to overcome MDR challenges. NEs can also minimize exposure of therapeutic cargo to normal tissues potentially reducing side effects. In >80% of ovarian cancers, Folate Receptor-α (FR-α) is expressed at 10- to 100-fold higher levels than on non-pathological tissues. Therefore, folate (FA) is being evaluated as an active targeting moiety for FR-α + ovarian cancer. To improve therapeutic outcome with reduced toxicity, we developed NMI-500, a FA targeted gadolinium (Gd) annotated NE loaded with docetaxel (DTX). NMI-500 has been developed as theranostic agents as Gd will enable physician to acquire real time pharmacodynamics data on NE + DTX accumulation in target lesions. In present study, characterization for key translational metrics of NMI-500 showed size distribution in range of 120 to 150 nm and zeta potential around −45 mV. Active targeting of FA was evaluated against FR-α + KB cells and results demonstrated significant improvement in cell association which was surface ligand density dependent. We found that NMI-500 was able to inhibit tumor growth in a spontaneous transgenic ovarian cancer model with improved safety profile and this growth inhibition could be longitudinally followed by MRI. These results indicate NMI-500 warrants advancement to clinical trials.